THE EFFECTIVENESS OF FLASH CARDS AT TEACHING MEDIA ON VOCABULARY BUILDING AT SMKS KESEHATAN KELUARGA BUNDA JAMBI IN THE 2019/2020 ACADEMIC YEAR - Rahmah Rahmah; Yulia Wiji Astika; Ahmad Najmi Syaifi (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2020)
English is a foreign language in Indonesia, it is taught from Junior High School to University. One important thing of teaching English is vocabulary. If the students could not master the vocabulary of English given in Junior High School, it possible happens that they will get some difficulties in mastering it in Senior High School. A common stereotype of people about vocabulary is a long list of words from a textbook, a list of spelling words, or even various glossaries that are studied for examination. This situation encourages many practitioners to use a variety of techniques to teach vocabulary. Usually, flash cards were the favorite technique in mind. The researcher  interests to appoint this problem by title: The Effectiveness of Flash Cards at Teaching Media on Vocabulary Building At SMKS Kesehatan Keluarga Bunda Jambi In The 2019/2020 Academic Year. The method had used in this research was descriptive quantitative. The population of this research was the students of SMKS Kesehatan Keluarga Bunda Jambi.The samples were 36 students of the first years. Consist of 16 male and 20 female. In this research, the instrument used to collectedthe data are observation, interview, with English teachers and documentation. The score r x y is 0,580, is bigger than score in level 5%=0,325 and 1%=0,418. It can be described as 0,3250,5800,814 in other word, there is significant effect by using flash cards on the student’s vocabulary building at SMSK Kesehatan Keluarga Bunda Jambi.